Effectiveness Of Education To Improve Ability Game For Children Learning Difficulties Additive (Study Case at SDN 1 Lamongan) - Barokati, Nisaul (STAI Miftahul Ula Nganjuk, 2015)
Abstract: This research is motivated by the childs learning disabilities who cannot do the sums 1-20. From roommates Researchers Gave test, the child cannot do the sums 1-20. This study aims to Prove the effectiveness of educational games for kids summation improves learning disabilities. Type of research is the Single Subject Research, with ABA design and the data analysis techniques using visual analysis chart. Measurement variables using a percentage of the number of questions answered the Correctly. From the results of this study indicate that effective educational games to Enhance the abilities of the sum of numbers for child learning disabilities in SDN 1 Lamongan So that educational games can be used as one solution to help improve the childs ability to sum numbers learning disabilities